Synergy of Technology and Pedagogy: A Review of Modern Learning Media in Primary Education - Gunawan Gunawan; Baiq Nabila Saufika Zainuri; Ni Made Yeni Suranti; Ida Ermiana (Indonesian Journal of Elementary and Childhood Education, 2026)
Digital transformation demands updated instructional strategies in elementary schools, yet practice shows a gap between technology availability and pedagogical use. This study maps the types, impacts, and implementation challenges of modern learning media at the elementary level through a synthesis of national and international literature. A systematic review guided by the PRISMA 2020 statement searched Google Scholar, Scopus, ScienceDirect, ERIC, SINTA/Garuda, and ProQuest. From 142 initial records, 29 primary studies and related reviews (2018-2025) met the inclusion criteria, supplemented by four theoretical-methodological references. Findings reveal ten media categories-including interactive presentation multimedia, digital e-books, gamification, augmented reality, mobile applications, web-based video, and e-learning-that consistently show positive effects on students' motivation, learning outcomes, and literacy, though magnitude varies by context and teacher readiness. Teachers' TPACK and regional digital-infrastructure gaps emerged as key determinants of successful integration. The study concludes that synergy between technological innovation and stronger teacher pedagogical capacity is essential for optimal, equitable use of modern learning media in elementary schools.